Synthesis of Allantoin Catalyzed by SO42-/La2O3-SiO2-ZrO2 - Liu, Lixiu; He, Aijiang; Li, Xiangbiao (Asian Journal of Chemistry, 2012)
Allantoin was synthesized using glyoxalic acid and urea as raw materials and La2O3-promoted solid acid SO42-/SiO2-ZrO2 as catalyst. The present research focused on the effects of La2O3 doping amount, catalyst dosage, reactant ratio and reaction temperature and time on the yield of allantoin. The optimum condition for reactions is as follows: amount of catalyst, 2.5 g; doping amount of La2O3, 0.12 wt %; molar ratio of reactants n(urea):n(glyoxylic acid) = 4:1; reaction temperature, 75 ºC and reaction time, 5 h. The yield of allantoin at optimum condition was up to 46 %. The melting point determination, infrared spectroscopy and elemental analysis of the product confirmed that the obtained product is allantoin and the analysis indicated that the purity was 98.5 % or above.